The Life and Work of Marquis Robert de Wavrin, an Early Visual Anthropologist. Issue 4 (7th August 2020) - Moderbacher, Christine; Winter, Grace
Abstract : This article traces the life and work of Marquis Robert de Wavrin de Villers au Tertre (1888–1971), a Belgian explorer and ethnographer. While fragments of his oeuvre are familiar to scholars of South America, he is almost completely unknown in historical studies, and largely forgotten within anthropology too. Here we will explore his filmic work as well as its contribution to the history of visual anthropology. While de Wavrin's work cannot be divorced from the discipline's colonial and Eurocentric heritage, we show that his visual record provides notable historic insights and merits further scholarly attention.